Smart Management of Healthcare Professionals Involved in COVID-19 Contrast With SWAPS - Bellavista, Paolo; Torello, Marco; Corradi, Antonio; Foschini, Luca (Frontiers in Sustainable Cities, 2021)
The recent COVID-19 pandemic in Italy has highlighted several critical issues in the management process of infected people. At the health level, the management of the COVID-19 positive was mainly delegated to the regional authorities and centrally monitored by the State. Despite requested common activities (such as diagnosis of virus positivity, active surveillance of infected people and contact tracing), Regional Health Departments were able to issue specific directives in their territories and establish priority levels for each activity according to the specific needs related to the emergency in their area. The development of novel digital tools for the management of infected people become an urgent necessity to foster more organized and integrated solutions, able to process huge amount of heterogeneous information. Mobile Crowdsensing methodologies could effectively facilitate needed lateral interviewing activities as well as the monitoring of crowds in environments with a high concentration of virus-positive subjects (such are hospital wards but also other locations), facilitating the tracing of possible outbreaks of contagion due to advanced geolocation techniques and big data analysis methods. This paper analyzes the functionality of SWAPS (Supporting Workflows for Healthcare Personnel management), a modular and scalable web platform developed by the University of Bologna specifically for the management of COVID positive personnel within healthcare facilities. It also analyzes the possible integrations between SWAPS and ParticipACT, an advanced MCS platform developed by the University of Bologna. This article surveys the current literature on software platforms to address COVID-19 and related tracing issues and presents the practical issues and on-the-field results obtained from the research developed by the University of Bologna by assisting the deployment of the proposed solution for a big Regional Health Department in the city of Bologna.